Perioperative passport: empowering people with diabetes along their surgical journey. Issue 12 (20th October 2017) - Page, E.; Akiboye, F.; Jackson, S.; Kerry, C.; Round, R.; Rayman, G.; ,
Abstract: Aim: To determine whether a handheld 'perioperative passport' could improve the experience of perioperative care for people with diabetes and overcome some of the communication issues commonly identified in inpatient extracts. Methods: Individuals with diabetes undergoing elective surgery requiring at least an overnight stay were identified via a customized information technology system. Those allocated to the passport group were given the perioperative passport before their hospital admission. A 26‐item questionnaire was completed after surgery by 50 participants in the passport group (mean age 69 years) and by 35 participants with diabetes who followed the usual surgical pathway (mean age 70 years). In addition, the former group had a structured interview about their experience of the passport. Results: The prevalence of those who reported having received prior information about their expected diabetes care was 35% in the control group vs 92% in the passport group ( P <0.001). The passport group found the information given significantly more helpful ( P <0.001), including the advice on medication adjustment ( P =0.008). Furthermore, those with the passport were more involved in planning their diabetes care ( P <0.001), less anxious whilst in hospital ( P <0.044) and better prepared to manage their diabetes on discharge ( P ≤0.001). The mean length of hospital stay was shorter in the passport group, although the difference did not reach significance (4.4 vs 6.5 days; P <0.058). Content analysis indicated that the passport was well liked and innovative. Conclusion: Our data indicate that the perioperative passport is effective in both informing and involving people in their diabetes care throughout the perioperative period. What's new?: We developed a perioperative passport as a novel approach to help overcome the disempowerment and poor communication that is often experienced by people with diabetes undergoing elective surgery. The passport contained essential information pertaining to a surgical inpatient stay and addressed common questions that patients may ask about their care. Quantitative and qualitative methods showed that the perioperative passport was effective in involving and informing people with diabetes undergoing elective surgery. The perioperative passport has the potential to be widely adopted by other National Health Service Trusts wishing to enhance their perioperative pathway for elective patients with diabetes.